Issue Information. Issue 1 (18th September 2020) - Unknown
Abstract : Cover : In Sweeney et al. (http://doi.org/10.1002/cpbi.104 ), the image shows RNAcentral genome browser showing several alternative precursor and mature sequences annotated by miRBase and MirGeneDB in a single genomic region. The highlighted transcript is URS0000530EBF_9606, the miRNA precursor from miRBase.